Does enjoyment mediate the effect of teachers' hard and soft skills on their students' motivation in the physical education setting? - Armando Cocca; Klaus Greier; Michaela Cocca; Gerhard Ruedl (Bern Open Publishing, 2024)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) states that quality physical education (QPE) is essential for promoting health in youth, and that teachers have a prominent role towards achieving it (UNESCO, 2015). Previous research linked PE teachers' hard and soft skills with their students' in-class motivation. Teachers can foster students' willingness to learning (Johnson, 2017) by using professional competences - hard skills - (Simón-Chico et al., 2023), and by promoting positive relationships - soft skills - (Opdenakker, 2023). However, the mechanism by which these skills affect students' motivation is unclear because other variables, such as, students' enjoyment, may intervene. In fact, based on the most recognized international motivation-focused theories, enjoyment is considered as one of the most prominent determinants of motivation (Hagger & Chatzisarantis, 2015). The aim of the present work was to analyse the mediation role of enjoyment towards PE in the relationship between teachers' skills and students' intrinsic motivation for PE. A total of 1,319 adolescents (girls = 51.8%, 14.28 ± 2.18 years) filled in the Intrinsic Motivation Inventory for PE (4 dimensions: interest in PE, perceived competence, importance attributed to PE, and tension felt during PE), the Teachers Personal and Professional Skills Questionnaire (2 dimensions: soft skills, and hard skills), and the Questionnaire for the Measurement of Enjoyment in PE in Adolescents (3 dimensions: pleasure, flow, and recreation). Regarding hard skills, results of the path analysis showed signs of mediation for flow (p = .035) and pleasure (p = .023) towards interest in PE, whereas the paths to perceived competence and importance attributed to PE were both fully mediated by pleasure (p = .032). Hard skills also directly increased students' perceived tension during PE (p = .017). Soft skills positively, directly, and indirectly (through all dimensions of enjoyment) affected students' interest in PE, importance attributed to PE, and students' tension during PE (p < .001), whereas their impact on perceived competence was fully mediated by all enjoyment dimensions (p < .05). Our outcomes confirm the key role of teachers' hard and soft skills, additionally supporting the idea that triggering enjoyment in students may lead to higher motivation to actively adhere to PE. In conclusion, the mediating role of enjoyment is confirmed in most of the paths leading to students' motivation for PE; hence, it is recommended that teachers focus on using both their sets of skills to propose fun and engaging activities, which may increase participation both on the short and long term. References Hagger, M. S., & Chatzisarantis, N. L. (2015). The trans-contextual model of autonomous motivation in education: Conceptual and empirical issues and meta-analysis. Review of Educational Research, 86(2), 360-407. https://doi.org/10.3102/0034654315585005 Johnson, D. (2017). The role of teachers in motivating the students to learn. BU Journal of Graduate Studies in Education, 9(1), 46-49. Opdenakker, M. (2023). Teacher and teaching behaviour and student motivational outcomes: Critical reflections on the knowledge base and on future research. In R. Maluana, M. Helms-Lorenz, & R. M. Klassen (Eds.), Effective teaching around the world (pp. 29-83). Springer. https://doi.org/10.1007/978-3-031-31678-4_3 Simón-Chico, L., González-Peño, A., Hernández-Cuadrado, E., & Franco, E. (2023). The impact of a challenge-based learning experience in physical education on students' motivation and engagement. European Journal of Investigation in Health, Psychology and Education, 13(4), 684-700. https://doi.org/10.3390/ejihpe13040052 United Nations Educational, Scientific and Cultural Organization. (2015). Quality physical education. UNESCO.